Produção de biomassa, composição química e decomposição de resíduos culturais da parte aérea e raízes no solo - Redin, Marciel (2014)
Crop residues (CR) from shoots (S) and roots (R) of plants are the main source of carbon C (C) and nitrogen (N) for the agricultural soils. Compared to the S of plants there are few studies on the production of dry matter (DM), C and N accumulation and decomposition of R. The decomposition of CR in soil is affected in part by its chemical composition, which can be affected by family and mixture of CR. The objectives of this study were as follows: a) evaluate the dry matter production (DM), chemical composition and accumulation of C and N in DM of S and R from 27 species of annual crops five families; b) relate the chemical composition of R from 20 species of annual crops with C mineralization in soil and c) study the interactions of additivity or non-additivity of the mineralization of C and N of CR of different chemical compositions (leaves and stems) on the surface of the soil. Three studies were realized: In the first study was quantified DM, accumulation of C and N in DM, chemical composition of S (leaves and stems) and R and the other two study was evaluated under laboratory conditions for 120 days, the mineralization of C and/or N of the CR in soil. The data measured of C mineralization were adjusted with a simple exponential model. Principal components analyses (PCAs) were performed to explore the qualitative address in CR and of decomposition. The DM of R, concentrated in the 0-10 cm layer, ranged from 0.54 to 1.44 Mg ha-1 in the legumes (Fabaceae) species and from 0.53 to 2.32 Mg ha-1 in the non-legumes (mainly Poaceae), corresponding the values between 63 to 97% of the total amount of roots in the 0-20 cm layer. The R/S ratio average was below legumes compared to non-legumes (0.14 times 0.20). The legumes acumulated in R 392 kg C ha-1 and 15 kg N ha-1 and the non-legumes 642 kg C ha-1 and 16 kg N ha-1. PCAs showed that the chemical composition of the S and R differentiated plant families. Mineralization of C of R ranged widely in terms of kinetics and the total amount of C mineralized (36% to 59%). The mineralization constant (k) was negatively correlated with hemicellulose and positively with the N content in R. R of Poaceae with high content of hemicellulose, cellulose and low total N showed a low value of k and cumulative mineralization C. The S of the legumes showed high total nitrogen, soluble compounds and greater differences between the chemical composition of leaves and stems. The Poaceae were characterized by high content of hemicellulose and cellulose, little difference between leaves and stems and slow decomposition. The mixture of leaves and stems showed mainly additives effects (no effect) in the mineralization of C and N in the soil. Antagonistic effect on N mineralization was observed in most Fabaceae mixtures with high content of N and heterogeneity between leaves and stems. Species of non-legumes produce more DM and C accumulation (1.8 times), high accumulation of N in R (1.3 times) and ratio R/S (1.6 times) than legumes. The decomposition of R species of annual crops is controlled by the content of cellulose and hemicellulose. The interactions of non-additivity related to decomposition of mixed of residues of leaves and stems are controlled by the degree of heterogeneity and N availability in the mixtures.